DEGRADATION OF BIODIESEL STORAGE AND ITS MICROBIAL IMPLICATION ON AISI 1020 STEEL AND 316L STEEL MATERIAL - Hugo Guillermo Jiménez Pacheco (2021)
In this paper, the characteristics of the physical-chemical degradation potential of soybean methyl biodiesel were studied, applied to samples of B100, B5, and diesel in storage tanks, including the analysis of microorganisms present in sample bodies with the correct corrosion measurement for AISI 1020 and 316L steel in different environments. Inside the tanks, immersion tests were performed on the sample body, maintaining storage conditions, dynamic conditions, and ambient temperature, for 120 days, collecting samples regularly to evaluate media degradation and analyze microorganisms to develop physicalchemical characterization, oxidation stability (OSI), and water content. Once the storage stage was completed, the corrosion ratio was measured in mm/ year according to ASTM D3707 and the presence of biological microorganisms.The oxidation stability of the B100 samples had a greater decrease than those of B5 and diesel. This shows that hydrocarbons depend on the metabolism of microorganisms, environmental conditions, feed conditions, and the amount of oxygen they contain. It has been shown that microorganisms contribute to the co-metabolism of storage tank surfaces. After an IFM optical digital evaluation, turbidity is observed in B100 biodiesel. These results were obtained for AISI 1020 and AISI 316L; there was no evidence of corrosion uniformity when tested by the IFM optical digital instrument. The results show the following range <2um, no affected location (pits), and corrosion rates were found to be negligible with a rate of <0.02 mm/year showing excellent corrosion resistance of the carbon steel, which meets the required experimental conditions. This means that the steel is suitable to withstand the storage conditions.